1997
DOI: 10.3354/meps160101
|View full text |Cite
|
Sign up to set email alerts
|

Growth and consumption rates of bacterivorous Antarctic naked marine amoebae

Abstract: This IS the first study to consider the growth and feeding rates of naked marine amoebae at temperatures below 5°C. Specific growth rates were calculated for 5 Antarctic isolates, Platyamoeba australis, A4ayorella sp., Metachaos sp., Vannella sp., and an unidentified vahlkampfiid amoeba. Growth rates ranged between 0.08 X 10-l and 2.9 X 10-' h" corresponding to generation times of 866.2 and 23.9 h, respectively. All isolates grew at temperatures down to -2OC and showed optimal growth at 2°C although one specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…In theory, a significant relationship between GGE and growth rates of protists would not be expected because, unlike large, multicellular organisms, protists do not have significant basal respiration (Fenchel, 1986). Published data indicate that GGE of protists may increase, decrease or remain unchanged with changes in temperature (Laybourn and Stewart, 1975;Rogerson, 1981;Rassoulzadegan, 1982;Verity, 1985;Caron et al, 1986;Choi and Peters, 1992;Mayes et al, 1997;Ishigaki and Sleigh, 2001). GGEs measured in this study yielded a relatively narrow range of values, which did not vary consistently with temperature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In theory, a significant relationship between GGE and growth rates of protists would not be expected because, unlike large, multicellular organisms, protists do not have significant basal respiration (Fenchel, 1986). Published data indicate that GGE of protists may increase, decrease or remain unchanged with changes in temperature (Laybourn and Stewart, 1975;Rogerson, 1981;Rassoulzadegan, 1982;Verity, 1985;Caron et al, 1986;Choi and Peters, 1992;Mayes et al, 1997;Ishigaki and Sleigh, 2001). GGEs measured in this study yielded a relatively narrow range of values, which did not vary consistently with temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported increases in GGE with decreasing temperature (Rassoulzadegan, 1982;Verity, 1985;Choi and Peters, 1992), whereas others have reported decreases with decreasing temperature or very low GGE at extreme low temperature (Laybourn and Stewart, 1975;Rogerson, 1981;Mayes et al, 1997). Still others have reported no effect of temperature on GGE (Caron et al, 1986;Ishigaki and Sleigh, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations